2014
DOI: 10.3390/s141222159
|View full text |Cite
|
Sign up to set email alerts
|

GPS & GLONASS Mass-Market Receivers: Positioning Performances and Peculiarities

Abstract: Over the last twenty years, positioning with low cost Global Navigation Satellite System (GNSS) sensors have rapidly developed around the world at both a commercial and academic research level. For many years these instruments have only acquired the GPS constellation but are now able to track the Global’naja Navigacionnaja Sputnikovaja Sistema (GLONASS) constellation. This characteristic is very interesting, especially if used in hard-urban environments or in hard conditions where satellite visibility is low. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…In this way, it was found that better than decimetre real-time on-the-fly positioning precision could be achieved. Dabove and Manzino (2014) discussed of the precision achievable using a low cost receiver; in this contexts the authors showed the level of precision was of few centimetres and the possible benefit of integration with other satellite constellations. Tsakiri, Sioulis, and Piniotis (2016) showed that the level of the accuracy is lower than 10 cm (3D positioning) and the "fixed" solutions were greater than 76%; specifically, in an open environment, the level of precision achievable was few centimetres.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, it was found that better than decimetre real-time on-the-fly positioning precision could be achieved. Dabove and Manzino (2014) discussed of the precision achievable using a low cost receiver; in this contexts the authors showed the level of precision was of few centimetres and the possible benefit of integration with other satellite constellations. Tsakiri, Sioulis, and Piniotis (2016) showed that the level of the accuracy is lower than 10 cm (3D positioning) and the "fixed" solutions were greater than 76%; specifically, in an open environment, the level of precision achievable was few centimetres.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] who have performed numerous tests in a variety of static and kinematic environments. However, there is a growing demand for the surveying community to ensure that the emerging technology of low-cost HS receivers can meet standards that guarantee reliable geodetic control work.…”
Section: Introductionmentioning
confidence: 99%
“…For solving these issues, one of these two principal approaches can be adopted, as widely described in the literature: the post-processing or real-time techniques. This last method can be used when the required accuracy has to be 5 cm at least [12], a condition that cannot be generally satisfied and obtained especially considering smart devices, such as smartphones or tablets [13,14].…”
Section: Gnss Positioning Technique With Smartphonesmentioning
confidence: 99%